Enhanced immunogenicity of CD4(+) t-cell responses and protective efficacy of a DNA-modified vaccinia virus Ankara prime-boost vaccination regimen for murine tuberculosis. - Mcshane, H; Brookes, R; Gilbert, S; Hill, A (2001)
DNA vaccines whose DNA encodes a variety of antigens from Mycobacterium tuberculosis have been evaluated for immunogenicity and protective efficacy. CD8(+) T-cell responses and protection achieved in other infectious disease models have been optimized by using a DNA immunization to prime the immune system and a recombinant virus encoding the same antigen(s) to boost the response. A DNA vaccine (D) and recombinant modified vaccinia virus Ankara (M) in which the DNA encodes early secreted antigenic target 6 and mycobacterial protein tuberculosis 63 synthesized, and each was found to generate specific gamma interferon (IFN-gamma)-secreting CD4(+) T cells. Enhanced CD4(+) IFN-gamma T-cell responses were produced by both D-M and M-D immunization regimens. Significantly higher levels of IFN-gamma were seen with a D-D-D-M immunization regimen. The most immunogenic regimens were assessed in a challenge study and found to produce protection equivalent to that produced by Mycobacterium bovis BCG. Thus, heterologous prime-boost regimens boost CD4(+) as well as CD8(+) T-cell responses, and the use of heterologous constructs encoding the same antigen(s) may improve the immunogenicity and protective efficacy of DNA vaccines against tuberculosis and other diseases.